IMATERALISASI JAMINAN BENDA DALAM BENTUK CASH COLLATERAL SEBAGAI JAMINAN PROYEK INFRA STRUKTUR MELALUI MEKANISME SWIFT - Murwaji, Tarsisius (Faculty of Law, Universitas Jenderal Soedirman, 2013)
The construction of infrastructure projects require large expenses. The cost for the project loan is usually derived from international banks. Legal issues, among others: we do not guarantee the legal system conducive to use in large financing; corporate body and banking institutions we considered to be of international standard, and our le-gal system is regarded as the country risk. The other hand many people of Indonesia who have collateral material, usually pure gold (precious metals) that have been diimaterialization and included in the accounts of foreign banks. Such guarantees may be used as the basis of the issuance of bank guarantees and through the mechanism of Society Worldwide Interbank Financial Telecommunications (SWIFT) can be used as loan collateral banks in Indonesia. Key words: bank guaranty, SWIFT, security law, international banking system